A self-assembled silicon/phenolic resin-based carbon core–shell nanocomposite as an anode material for lithium-ion batteries. Issue 7 (17th January 2018) - Lu, Zhiyao; Li, Bing; Yang, Daijun; Lv, Hong; Xue, Mingzhe; Zhang, Cunman
Abstract : A self-assembled silicon/phenolic resin-based carbon core–shell nanocomposite is reported, which exhibits a high and stable reversible capacity and good rate capability. Abstract : Silicon, with advantages such as high theoretical capacity and relatively low working potential, has been regarded as promising when it is used for lithium-ion battery anodes. However, its practical application is impeded by the intrinsic low electrical conductivity and the dramatic volume change during the lithiation/delithiation process, which leads to a rapid capacity fading of the electrode. In this regard, we design silicon nanoparticles homogeneously coated with a phenolic resin-based carbon layer as a core–shell nanocomposite via a facile self-assembly method followed by carbonization. The surrounding carbon shell, confirmed by transmission electron microscopy and Raman spectroscopy, is not only beneficial to the formation of a stable solid electrolyte interface film, but the electrical conductivity of the electrode is also enhanced. A high and stable specific capacity of nearly 1000 mA h g −1 is achieved at C/3 after 200 cycles with a coulombic efficiency of >99.6%. The entire synthesis process is quite simple and easy to scale up, thus having great potential for commercial applications.